Investigations on train‐induced vibration and vibration control of an over‐track building using thick‐layer rubber bearings. (12th October 2021) - Zhou, Ying; Ma, Kaiqiang; Chen, Peng; Lu, Decheng; Wu, Hao
Abstract: A large number of over‐track buildings have been designed in metropolis during the recent decades for adapting to rapid urbanization and saving land resources. However, the over‐track buildings are potentially affected by train‐induced vibration that may cause discomfort or health problem for residents, which in turn needs to be carefully evaluated. In this study, the responses of a high‐rise over‐track building with three different transfer types have been investigated using the recorded three‐dimensional accelerations from in‐situ tests. By performing time history analyses, the vibration responses of the fixed structure, traditional rubber bearing (TrRB) isolated, and thick‐layer rubber bearing (ThRB) isolated structures are analyzed and evaluated, respectively. The results show that the most evident vibration is in the vertical direction with vibration energy mainly concentrated among the high frequencies. Thereafter, the effects of vibration control by using different isolation technologies are compared. It is demonstrated that the abilities to isolate vertical train‐induced vibration could be enhanced by using ThRB while the horizontal isolation performance is still guaranteed. Then the reason for the variation of vibration amplitude along the building height is discussed. This research enriches the train‐induced vibration database and exemplifies the vibration mitigation control and design for over‐track buildings.